Littoral Cell Angioma in a Patient with Crohn’s Disease - Joel Johansson; Bergthor Björnsson; Simone Ignatova; Per Sandström; Mattias Ekstedt (Case Reports in Gastrointestinal Medicine)
Littoral cell angioma is a rare vascular tumor of the spleen. The pathogenesis is unknown but the lesion is associated with several malignancies and immunological disorders. The diagnosis requires histopathological examination. The malignant potential of this lesion is unknown, which is why splenectomy is recommend for all cases. Symptomatic cases generally suffer from hypersplenism and pyrexia. A previously healthy 20-year-old female was diagnosed with colonic Crohn’s disease; as part of the work-up a magnetic resonance enterography was performed which showed multiple signal changes of the spleen. The patient reported chronic abdominal pain in the left upper quadrant, malaise, and fever. The unknown splenic lesions prompted a laparoscopic splenectomy; pathology revealed a littoral cell angioma. The abdominal pain and malaise remitted but the fever persisted one year despite adequate treatment of the patient’s Crohn’s disease. Littoral cell angioma is associated with immune-dysregulation including Crohn’s disease with several reported cases. Signs and symptoms of hypersplenism and splenic lesions on imaging should raise suspicion of littoral cell angioma in patients with Crohn’s disease. Magnetic resonance enterography to assess disease severity in Crohn’s disease may provide an opportunity to study the prevalence and natural history of this rare splenic tumor.